Deterioration of AHG (Factor VIII) and Fibrinolysis - Brakman, P; van Creveld, S; Engelsman, E; van’t Laar, A; Mochtar, I. A; Veder, H. A (Thrombosis and Haemostasis, 1959)
The possible relationship between antihemophilic globulin (Factor VIII) and fibrinolysis was investigated. No conclusive evidence about the role of fibrinolysis in the deterioration of AHF was obtained but the findings were more against than in favour of the role of fibrinolysis.